A combination of fins-nanoparticle for enhancing the discharging of phase-change material used for liquid desiccant air conditioning unite. (August 2019) - Abdulateef, Ammar M.; Abdulateef, Jasim; Al-Abidi, Abduljalil A.; Sopian, Kamaruzzaman; Mat, Sohif; Mahdi, Mustafa S.
Highlights: A combination of fins-nanoparticle is studied numerically and experimentally. TTHX with longitudinal fins and TTHX with triangular fins are separately analyzed. The solidification rate was minimized as the angle direction increased. An important enhancement for PCM discharging was with nanoparticle. Abstract: A combination of fins-nanoparticle is essential for enhancing the Thermal Energy Storage (TES) that reduces the mismatch between energy supply and energy demand and this employs for Liquid Desiccant Air Conditioning Unite. Major problem is that most Phase-Change Materials (PCMs) have low thermal conductivity ( k ≤ 0.2 W/m K), resulting in an incomplete charging and discharging processes. Triplex-Tube Heat Exchanger (TTHX) was numerically and experimentally designed, adopted and tested with Alumina nanoparticle (Al2 O3 ) and Paraffin (RT82) that has a discharging temperature of 65 ° C . The both-sides freezing was used as a major method and the experimental findings displayed the influence of mass flow rates on the PCM discharging basing on the change in these rates of 16.2, 29.4 and 37.5 kg/min, respectively. The solidification rate was minimized as the angle direction increased from θ  = 90° to θ  = 270°. Other important findings were that with fins-nanoparticle, an enhancement for the cooling rate of the PCM, compared with these without nanoparticle. Furthermore, the PCM model was solved by the enthalpy-porosity and the finite-volume methods with the Software Ansys Fluent. The solidification time was reduced for TTHX with longitudinal fins and TTHX with triangular fins to 33% and 34% under the effect of 10% nanoparticle, compared with pure Paraffin, respectively. The total energy released for the PCM and nano-PCM was considered. Close agreement obtained between numerical and experimental findings.